Minority governments and legislative reliability: Evidence from Denmark and Sweden - Klüver, H; Zubek, R (SAGE Publications, 2017)
When are minority cabinets effective? We study the extent to which minority cabinets demonstrate legislative reliability, that is, introduce to parliament the bills they have announced in their legislative agendas. We test hypotheses drawn from two theories of minority government effectiveness: the positional agenda power theory which emphasizes the central location of the minority cabinet in the policy space and the ideological proximity theory which stresses the importance of the ideological closeness of opposition parties to the government. In an analysis of over 1600 bills announced by Danish and Swedish minority cabinets in 19 legislative agendas published between 1998 and 2012, we find more support, overall, for the ideological proximity than for the positional agenda power model.